The Sagittal Parameters and Efficacy of Pedicle Subtraction Osteotomy in Patients with Ankylosing Spondylitis and Kyphosis Under Different Lumbar Sagittal Morphologies - Zhang PC; Deng Q; Sheng WB; Guo HL; Mamat M; Luo YX; Gao ST (International Journal of General Medicine, 2021)
Peng-Chao Zhang, Qiang Deng, Wei-Bin Sheng, Hai-Long Guo, Mardan Mamat, Yun-Xiao Luo, Shu-Tao Gao Department of Spine Surgery, The First Affiliated Hospital of Xinjiang Medical University, Urumqi, 830054, People’s Republic of ChinaCorrespondence: Qiang DengDepartment of Spine Surgery, The First Affiliated Hospital of Xinjiang Medical University, No. 137 of Liyushan South Road, Xinshi District, Urumqi, 830054, People’s Republic of ChinaTel +86 13325636562Email dengqiang_abc@163.comObjective: This study aimed to compare the changes in sagittal parameters and the efficacy of pedicle subtraction osteotomy (PSO) in patients with ankylosing spondylitis (AS) and kyphosis under different lumbar sagittal morphologies and to explore the effect of sagittal morphology on the selection of PSO levels.Methods: A total of 24 patients with AS and thoracolumbar kyphosis (TK) who were admitted to the First Affiliated Hospital of Xinjiang Medical University between 2008 and 2019 were enrolled in this study. They were divided into two groups: a lumbar lordosis group (n = 14) and a lumbar kyphosis group (n = 10). Changes in sagittal parameters, lumbar Japanese Orthopaedic Association (JOA) scores, and visual analog scale (VAS) scores for lumbar pain before and after operation were compared between the two groups to evaluate postoperative efficacy.Results: The preoperative lumbar lordosis (LL) was − 29.29 ± 5.40 (lordosis) and 13.50 ± 3.65 (kyphosis) (P < 0.01), and the preoperative sagittal vertical axis (SVA) was 171.35 ± 25.46 (lordosis) and 223.58 ± 21.87 (kyphosis) (P < 0.01). Preoperative global kyphosis (GK) was 75.71 ± 5.26 (lordosis) and 86.30 ± 10.32 (kyphosis) (P < 0.05). All patients in the lordosis group underwent PSO surgery at the twelfth thoracic vertebra (T12) or the first lumbar spinal vertebra (L1), while all patients in the kyphosis group underwent the surgery at the second or third lumbar spinal vertebra (L2 or L3). The differences in postoperative GK, LL, and SVA between the two groups were not significant (P > 0.05). The JOA scores of the two groups increased from 13.00 ± 0.83 (lordosis) and 11.30 ± 0.93 (kyphosis) before surgery to 21.00 ± 0.67 and 19.70 ± 0.60 after surgery (P < 0.05).Conclusion: Preoperative lumbar sagittal morphology needs to be considered when selecting the optimal osteotomy plane. An osteotomy can achieve the greatest success in patients with lumbar kyphosis at L2/L3; for patients with lumbar lordosis, it can achieve satisfactory outcomes at T12/L1.Keywords: ankylosing spondylitis, kyphosis, sagittal parameters, PSO, osteotomy